2021
DOI: 10.1016/j.jsmc.2021.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Sleep, Wakefulness, and Circadian Functions in Neurologic Disorders

Abstract: Neurologic disorders impact the ability of the brain to generate sleep, wake, and circadian functions. Preexisting or de novo sleep-wake-circadian pathologies are generally underdiagnosed in neurologic patients despite their major impact on onset, evolution, and outcome of neurologic disorders. Neurologic disorders are frequently accompanied by sleep-wake EEG changes. Extensive brain damage can lead to the absence of measurable differentiation between sleep and wakefulness (status dissociatus). New technologie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 97 publications
(130 reference statements)
0
4
0
Order By: Relevance
“…La fase REM (considerada esencial para los fenómenos de neuroplasticidad) junto con los husos de sueño, reflejan la activación del sistema tálamo-cortical y desempeñan un papel fundamental en la consolidación de la memoria y de tareas motoras simples durante el sueño en individuos sanos [33][34][35][36][37].…”
Section: Discussionunclassified
“…La fase REM (considerada esencial para los fenómenos de neuroplasticidad) junto con los husos de sueño, reflejan la activación del sistema tálamo-cortical y desempeñan un papel fundamental en la consolidación de la memoria y de tareas motoras simples durante el sueño en individuos sanos [33][34][35][36][37].…”
Section: Discussionunclassified
“…However, it is worth noting that our study results were consistent with those of other studies regarding the association between stroke type and sleep duration [ 10 , 21 ]. Third, the sleep disorder-related variables were also self-reported; however, early studies have shown that self-reported sleep duration was consistent with the sleep duration obtained through actigraphy monitoring [ 13 , 36 ]. Fourth, this study was a cross-sectional study, and there was a certain limitation in determining the causal relationship between sleep-related variables and stroke.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, sleep-wake cycles and circadian disorders have been increasingly recognized as risk factors for stroke [ 11 , 12 ]. Therefore, the diagnosis and treatment of sleeping disorders should be considered as a prevention and intervention of stroke [ 13 ]. Although there have been many advances in determining various stroke-related risk factors based on sleeping, previous studies have mostly focused on sleep apnea syndrome and sleep duration, and other sleep quality-related indicators were rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…The tumor process and severe brain damage have different mechanisms of circadian rhythm disturbances, affecting intracellular oscillators in the first case, and central oscillators in the second, destroying the circadian rhythms in the pathological brain [ 10 , 11 ]. The study of circadian rhythms in the brain could be useful for predicting the course and outcomes of the disease, including cerebral accidents.…”
Section: Introductionmentioning
confidence: 99%